The Role of AI in Transforming Global Development and Society - Gaev, Danka; Petković, Jasna; Lečić Cvetković, Danica (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Technological trends drive change and innovation, shaping how we live, work, and communicate. Artificial intelligence (AI) stands out by transforming society, enhancing work, learning, and daily life. Its adoption across sectors improves efficiency, personalizes processes, and expands resource access. While developed countries rapidly adopt AI technologies, less developed nations face challenges like infrastructure gaps, limited resources, and digital illiteracy, creating a significant development gap. This paper explores AI potential by comparing practices between developed and less developed countries, aiming to identify best practices for inclusive technology application. Special attention is given to the importance of understanding AI’s impact on society’s future. The paper emphasizes that AI integration is not just a technological challenge but a social responsibility, as it can reduce global inequalities and improve quality of life. Recommendations for strategic AI implementation are provided to minimize risks and negative consequences from improper application and regulation.